A semiotic landscape analysis of the film posters: Parasite, Mother and Whiplash - H. Can Boysan; Nalan Kiziltan (Literacy Trek, 2023)
The aim of this study is to discuss the film posters of Parasite, Mother and Whiplash through semiotic landscape. The analyses have been based on Halliday's Functional Grammar (1985) and, Kress and van Leeuwen's Visual grammar (2020). The film Parasite has been analysed within the actional and classificational processes, whereas the film Mother has been examined within the reactional and analytical processes and the film Whiplash has been investigated through the speech and mental processes, and the symbolic processes. The film posters have been also discussed in terms of the descriptive and connotative meanings, as well as the significance of colours in conveying emotions and cultural meanings. Besides, the widespread use of disguised symbols has been identified in film posters. This study sheds light on the influence of visual discourse analysis on film posters, emphasizing the study of semiotics and visual communication in a media-dominated society.